Ab initio stability predictions for rare earth oxyphosphates and experimental confirmation of cerium (III) phases - Edric X. Wang; Sergey V. Ushakov; Ligen Wang; Jared Matteucci; Hongwu Xu; Elizabeth J. Opila; Qi-Jun Hong; Alexandra Navrotsky (Proceedings of the National Academy of Sciences, 2025)
Rare earth oxyphosphates represent a large family of compounds with the general formula (RE 2 O 3 ) x (REPO 4 ), where RE refers to lanthanides and yttrium. At least four known stoichiometries have been established, each with distinct structures. These compounds have potential applications as refractory coatings, catalysts, and magnetic materials. We modeled the stability of RE 3 PO 7 [RE 3 (PO 4 )O 3 ] with respect to rare earth sesquioxides (RE 2 O 3 ) and orthophosphates (REPO 4 ) using DFT computations with the GGA-PBE and r2SCAN exchange-correlation functionals. Phase stability predictions were consistent between the two functionals, while r2SCAN calculations of formation enthalpies for REPO 4 showed better agreement with experimental data. RE 3 PO 7 phases for La–Dy were predicted to be stable at 0 K, with a space group change from Cm to C 2 /m starting with Sm. RE 3 PO 7 phases for Y, Ho, and Er were found to be stabilized by lattice vibrational entropies at temperatures above 800 K, 1,000 K, and 1,600 K, respectively. The formation of predicted cerium (III) oxyphosphate, isostructural to Nd 3 (PO) 4 O 3 , was confirmed through laser melting of monazite (CePO 4 ). Ce 3 (PO 4 )O 3 is monoclinic (space group Cm ) with experimentally measured cell parameters a = 12.989(1) Å, b = 13.413(1) Å, c = 12.396(1) Å, β = 108.06(1)°. The existence of a Ce member of RE 7 P 3 O 18 family with unknown structure was experimentally established. This work invites further exploration of RE oxyphosphates as functional materials and indicates the possible formation of Ce oxyphosphate upon monazite melting during impact events and their potential use in geothermometry.